SimFection: a digital resource for vaccination education. Issue 2 (15th March 2019) - Carolan, K.; Verran, J.; Amos, M.; Crossley, M.; Redfern, J.; Whitton, N.; Louttit, D.
Abstract: Vaccination coverage in the United Kingdom is below the level recommended by the World Health Organisation, and when vaccination coverage is not sufficient, outbreaks of infectious diseases can occur. In 2015, coverage of the first dose of the Measles-Mumps-Rubella vaccine declined in the United Kingdom for the first time since 2008, indicating a need to raise public awareness and understanding of the importance of vaccination to public health. Identifying 16 – 18-year olds as a target audience, being future parents who would make decisions regarding vaccination of their children, a digital educational resource ('SimFection') was developed to deliver key messages about the spread and control of vaccine-preventable infectious diseases (identified via school curricula). The process of development utilised an iterative approach, involving a cyclic process of prototyping, testing, analysis and refinement with a range of audiences including students, schoolchildren, and trainee teachers. The completed resource is now available online for free download.